2003
DOI: 10.1177/15910199030090s121
|View full text |Cite
|
Sign up to set email alerts
|

Coil Retrieval following Embolization of Cerebral Aneurysms

Abstract: Failed coil embolization of cerebral aneurysms may be occasionally followed by direct surgical treatment. We had 5 patients who underwent coil retrieval and surgical clipping after coil embolization because of periprocedural complications. The patients, ranging in age from 40 to 71, had wide-neck aneurysms located at the anterior communicating artery (AcomA) in 3 patients, the middle cerebral artery (MCA) in 1, and the internal carotid-ophthalmic artery (IC-Ophthalmic) in 1. They were embolized with G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Severe neurological consequences have been described in other reports. 4,6,7 One case demonstrated that coil migration represents a rare but potentially severe complication of cerebral aneurysm embolization. A man with subarachnoid hemorrhage had a delayed (8 days after the procedure) migration of a coil loop after adjunctive balloon remodeling of an anterior communicating artery (AComA) aneurysm causing ischemia on the anterior cerebral artery and paresia of the lower extremity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Severe neurological consequences have been described in other reports. 4,6,7 One case demonstrated that coil migration represents a rare but potentially severe complication of cerebral aneurysm embolization. A man with subarachnoid hemorrhage had a delayed (8 days after the procedure) migration of a coil loop after adjunctive balloon remodeling of an anterior communicating artery (AComA) aneurysm causing ischemia on the anterior cerebral artery and paresia of the lower extremity.…”
Section: Discussionmentioning
confidence: 99%
“…There was reversal of symptoms, because the main source of ischemic symptoms is the formation of small emboli around the migrated spirals. 4 Ding et al 8 identified 16 publications with 37 reported cases of migrated coil retrieval consisting of 10 case reports and 6 case series. Most of the aneurysms presented with rupture (65%) and were located in the anterior circulation (70%), but the migration occurred and was seen during the procedure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations